Future model of research and innovation in creative industries - Ahmad Rasdan Ismail; Abu Hassan Hasbullah; Khairul Azhar Mat Daud; Nik Zulkarnaen Khidzir; Suriatini Ismail; Mohd Firdaus Mahamad Ali (Universiti Malaysia Kelantan, 2014)
The rapid progression of creative industries in the 21st century has opened up doors of opportunities especially in employments thus contributing significantly to the growth of a country’s economy. This development has given rise to the phenomenon of “creative futures” of the 21st Century in which at the same time meteoric advancement in science and technology is taking place with the invention of a variety of communication networks and new media where the internet has been, by far, the most important feature of living systems. Generally, creative industries are to be associated with human creation, publishing or production, circulation or distribution, exchange or exhibition, consumption of goods and to provide attorney/services in order to feed cultural, artistic, aesthetic, intellectual, and emotional to customers in the market. Further in cultural processes such as design aims at bringing out a strong impression in all aspects of life directly affiliated with the consumption of commodities. This paper intentionally to address the new integration model of research and innovation that able to integrate the multiple discipline of knowledge and synergy the output of research and innovation through commercializations.